Diversity Management in Action: Chief Diversity Officer Adoption in America's Cities. (June 2019) - Cooper, Christopher A.; Gerlach, John D.
One of the primary ways cities signal the importance of diversity is to hire a chief diversity officer (CDO). Despite the importance of this position, we know remarkably little about the prevalence and predictors of CDO adoption in local governments. Using original data from the 250 largest cities in the United States, this article demonstrates that about one in four cities has hired a CDO. Further, the decision to hire a CDO is driven more by constituent demand than by city structure or resources. The article concludes by discussing the future of diversity management in America's cities.